ANGIOGRAPHIC STUDY OF CORONARY GRAFTS - Nadeem, Asif (Pakistan Armed Forces Medical Journal, 2018)
In last couple of decades, the number of ‘graft study’ cases in cath labs has increased due to increasing number of post coronary artery bypass surgery cases presenting with angina or ischemia. Coronary angiography in the setting of coronary artery bypass grafting (CABG) is an important diagnostic tool for the evaluation of graft patency in such patients. Angiography in the setting of CABG is more complex and challenging than the conventional angiography, but with increasing experience, the procedure can be made easy, sleek and comfortable both for the patient and for the operator.